Anisotropic stress as signature of non-standard propagation of gravitational waves - Saltas, Ippocratis D.; Sawicki, Ignacy; Amendola, Luca (Arxiv, 2014)
We make precise the heretofore ambiguous statement that anisotropic stress is a sign of a modification of gravity. We show that in cosmological solutions of very general classes of models extending gravity --- all scalar-tensor theories (Horndeski), Einstein-Aether models and bimetric massive gravity --- a direct correspondence exists between perfect fluids apparently carrying anisotropic stress and a modification in the propagation of gravitational waves. Since the anisotropic stress can be measured in a model-independent manner, a comparison of the behavior of gravitational waves from cosmological sources with large-scale-structure formation could in principle lead to new constraints on the theory of gravity.
Gesehen am 16.11.2017